Cosmic enigmas - Silk, Joseph, 1942- (New York : AIP Press, 1994)
"Archeology is the science that probes the past few thousand years. Geology takes us back two or even three billion years. Beyond that is the realm of cosmology: the study of the beginnings of the Universe around us.".
So begins a journey deep into the origins of time, the birth of galaxies, and all the way to the farthest realm, beyond the end of it all. The tour starts at the beginning, the very early Universe - with Silk's masterful account of the Big Bang Theory, culminating in the 1965 discovery of cosmic microwave background radiation. "This whisper of creation is the greatly faded relic of the primordial fireball..."
The Dark Cloud Revisited / Joseph I. Silk and Cedric Lacey -- The Invisible Universe / Joseph I. Silk and John D. Barrow -- From Quark to Cosmos / Joseph I. Silk and John D. Barrow -- The Missing Mass - Now It's a Gravitino! -- Great Voids in the Universe -- The Intergalactic Medium -- Dark Matter Comes in from the Cold -- Cosmology Back to the Beginning -- Probing the Primeval Fireball -- An Infrared View of the Universe -- Dark Matter Detected?
Includes bibliographical references and index.
Keywords: Cosmology; Astrophysics